2017
DOI: 10.1007/s00268-017-3949-z
|View full text |Cite
|
Sign up to set email alerts
|

Primary Surgery for Malignant Large Bowel Obstruction: Postoperative Nasogastric Tube Reinsertion is Not Mandatory

Abstract: Nasogastric tube reinsertion was not affected by immediate removal of the tube. Left-sided tumours and patients at risk of postoperative ileus should be managed with caution. Immediate nasogastric tube removal is not contraindicated in the case of large bowel obstruction because it is not associated with a higher risk of NGT reinsertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
(28 reference statements)
0
14
0
1
Order By: Relevance
“…However, there is growing evidence supporting the avoidance of NGT insertion in emergency laparotomy. For example, Venara et al[38] examined the results of immediate postoperative removal of NGT after emergency colectomy for malignant large bowel obstruction. Of note, only 10% of 79 studied patients had no postoperative NGT.…”
Section: Application Of Eras Items In Emergency Colorectal Surgery Anmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is growing evidence supporting the avoidance of NGT insertion in emergency laparotomy. For example, Venara et al[38] examined the results of immediate postoperative removal of NGT after emergency colectomy for malignant large bowel obstruction. Of note, only 10% of 79 studied patients had no postoperative NGT.…”
Section: Application Of Eras Items In Emergency Colorectal Surgery Anmentioning
confidence: 99%
“…Interestingly, the immediate removal of NGT and inclusion in ERAS protocol were not associated with the need for NGT reinsertion. Meanwhile, risk factors for NGT reinsertion were left-sided colon cancer, postoperative ileus and severe postoperative complications[38]. A randomized controlled trail examining the effect of prophylactic NGT decompression after emergency laparotomy for generalized peritonitis and intestinal obstruction indicated that routine NGT insertion did not prevent gastrointestinal discomfort or anastomotic leakage[39].…”
Section: Application Of Eras Items In Emergency Colorectal Surgery Anmentioning
confidence: 99%
“…We identified 3 SRs (2 older, overlapping SRs were excluded 113,114 ), 1 RCT, and 1 observational study assessing NGT use. [115][116][117] The SRs (37 studies) comparing routine and selective/no NGT use after elective and emergent abdominal operations found earlier return of bowel function (p < 0.00001) and decreased pulmonary complications (p ¼ 0.09) in the selective/no NGT group, but no differences in wound infection (p ¼ 0. 39…”
Section: Evidencementioning
confidence: 99%
“…(110, 112) A recent RCT of emergency laparotomy found no differences in nausea, vomiting, or abdominal discomfort (p ¼ 0.38); wound (p ¼ 0.30); respiratory complications (p ¼ 0.30); anastomotic leak (p ¼ 0.64); return of bowel function (p ¼ 0.54); or NGT reinsertion (p ¼ 0.43) between NGT and no NGT groups, but longer LOS in NGT group (7.52 vs 6.53 days; p < 0.05) 116. Finally, an observational study evaluated immediate removal of NGT postoperatively as part of an ERP after emergency operations for malignant large bowel obstruction and found that reinsertion was not associated with either immediate NGT removal (p ¼ 0.87) or ERP participation (p ¼ 0.75) 117.…”
mentioning
confidence: 99%
“…Oliveira Filho et al 22 Não se deve negar cirurgia de emergência em pacientes oncológicos, mesmo naqueles com doença em atividade Poon et al 23 Ressecção primária e anastomose de emergência podem ser realizadas com resultados favoráveis na maioria dos idosos com carcinoma colorretal obstrutivo esquerdo Scholefield et al 24 Rastreamento de câncer colorretal com exame de sangue oculto nas fezes pode reduzir casos de emergência com câncer colorretal Negoi et al 25 ; Repse et al 26 ; Shah et al 27 ; Smothers et al 28 Cirurgia de emergência tiveram maior chance de complicações, mortalidade, insucesso e internação prolongada Bocic et al 29 Mortalidade por câncer intestinal em cirurgia de emergência é multifatorial, envolvendo o status basal do paciente, decisão técnica cirúrgica e etiologia da obstrução Venara et al 30 Remoção imediata da sonda nasogástrica é indicada no caso de obstrução do intestino grosso Sabando et al 31 ; Abelson et al 32 Obstrução intestinal representou a maioria dos casos de abdome agudo com suspeita de neoplasia, perfuração duodenal, apendicite aguda e perfuração gástrica Frago et al 33 ; Lim et al 34 O implante de stent em pacientes com câncer colorretal obstrutivo, estágio IV paliativo, pode ser menos bem-sucedido do que se pensava Ho et al 35 Cirurgia eletiva pode ser mais segura, com menor morbidade e mortalidade quando comparada à prática atual de cirurgia de urgência Alcantara et al 36 ; Young et al 37 ; Ji et al 38 ; Kim et al 39 ; Law et al 40 Stent metálico autoexpansível não afeta a taxa de criação do estoma, possibilita cirurgia eletiva minimamente invasiva e diminui as complicações pós-operatórias Quadro 2. Principais desfechos e referências dos estudos encontrados para as emergências obstrutivas-estruturais do trato gastrintestinal.…”
Section: Principais Desfechosunclassified